HPLC-UV PROFILING OF BIOPHARMACEUTICALS AND IN-VITRO ANTIDIABETIC PROPERTIES OF ETHANOL EXTRACT OF ANNONA MURICATA LEAVES - OMINYI MATTHIAS CHUKWUEMEKA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to identify and quantify the phytochemical compounds and vitamins present in the ethanol extract of Annona muricata leaves and investigate on its antidiabetic potential. Methods: The plant bioactive compounds and vitamin contents of the extract were analyzed using high-performance liquid chromatography-ultraviolet (HPLC-UV) analytical methods. The antidiabetic potential of the extract was evaluated through in vitro assays of α-amylase and α-glucosidase inhibitory activities. Results: The HPLC-UV profiling revealed the presence of 19 bioactive compounds in the extract. Resveratrol (20.68 ppm) was the most abundant followed by steroids (14.65 ppm) and spartein (10.92 ppm). Flavan-3-ol (7.56 ppm) and proanthocyanidins (7.29 ppm) were moderately abundant. The extract also contained significant (p<0.05) quantities of water-soluble and fats-soluble vitamins. Among the water-soluble vitamins were B9 (0.0471 ppm), B1 (0.0470 ppm), B12 (0.0272 ppm), B6 (0.0198 ppm), B2 (0.0194 ppm), and the least in concentration was the B3 (0.0144 ppm). The most significant (p<0.05) in the order of abundance of the fats-soluble vitamins was calciferol (2.47 ppm), followed by tocopherol (0.63 ppm) and retinol (0.42 ppm) while the least was carotenoids (0.19 ppm). The extract also exhibited significant (p<0.05) percent of α-amylase inhibitory activity, but the effect was not concentration-dependent. However, the α-glucosidase inhibitory activity of the extract was concentration-dependent. Conclusion: The ethanol extract of A. muricata leaves has shown a significant (p<0.05) bioactive profile, with rich vitamin compositions, and exhibited a considerable percentage of antidiabetic activities. These findings suggest the therapeutic potential of the extract for management of diabetes and other disorders.